Methods of Strength Development in Middle Schoolers - Нарижний, В. О. (Physical Education Theory and Methodology, 2015)
Strength being the foundation of motor abilities development, the question arises as to rationalizing the process of its development. The purpose of the research is to improve the conventional methods of strength development in middle schoolers. To achieve the objectives set, the study used the following methods: theoretical analysis and collation of methodological literature, testing, pedagogical experiment, methods of mathematical statistics. Research results. The analysis of the testing results showed a statistically significant increase in the indicators by two of five tests in girls and three of five tests in boys, with the combined method used. The other results show a tendency to improve too, but the deviations in the testing results are statistically weak. The re-use of the method reveals a statistically reliable indicator in one of five exercises, whereas no such indicator manifests in girls. Conclusions. Using the combined method makes it possible to simultaneously influence several types of strength, which rationalizes the development of strength abilities. The tests “bending and unbending of arms in suspension lying”, “remaining in suspension lying on bent arms” proved most informative.